Sistemática da família Pimelodidae Swainson, 1838 (Teleostei: Siluriformes) - Rocha, Marcelo Sales (Instituto Nacional de Pesquisas da Amazônia - INPA, 2012)
The catfish family Pimelodidae currently comprises about 100 valid species and although its monophyly has been corroborated by some authors, the relationships within the family are poorly known, and derived features for some genera are lacking. A phylogenetic analysis of Pimelodidae was performed based on 145 morphological characters and 75 terminal taxa, representing 64 valid species. Ougroup species comprised Pimelodidae (5), Heptapteridae (3), Ictaluridae (1), Bagridae (1) and Diplomystidae (1, used as root). A most parsimonious cladogram was produced, with 442 steps, CI = 0.37, RI=0.78. A sister group relationship between Pimelodidae and Pseudopimelodidae was recovered and based on three synapomorphies: 1. posterior fontanel reduced; 2. ectopterigoid present; 3. swimbladder constrictor muscle present. Seven synapomorphies were found to corroborate the monophyly of Pimelodidae: 1. elongated surface on lateral ethmoid for the autopalatine; 2. infraorbital 1 connected to lateral ethmoid by cartilage; 3. vomer toothed; 4. presence of a pair of processes on the dorsal surface of premaxilla, where the proximal portion the maxilla fits; 5. dendritic arrangement of the cephalic canal lateral line tubes in the skin of the head and anterior trunk; 6. position of right cardinal vein foramen on vertebra 6; 7. deep sutural joint between the fifth and sixth centra. Some clades within family were found: Phractocephalinae (comprising Steindachneridion, Phractocephalus, Leiarius and Perrunichthys), is the sister group of the remaining Pimelodidae ( Neopimelodine ). Within Neopimelodine , two major groups are present Sorubiminae (Zungaro, Hemisorubim, Sorubim, Pseudoplatystoma, Hypophthalmus, Brachyplatystoma and Platynemathychthys) and a large and unnamed group, comprising Platysilurus, Platystomatichthys, Duopalatinus emarginatus, Pimelodus ornatus, Bagropsis, Pimelodus atrobrunneus, Pimelodus paranaensis, Calophysus group, Pimelodus group, and Exallodontus group. The Calophysus groups contains Pimelabditus, Cheirocerus, Pimelodina, Calophysus, Pinirampus, Aguarunichthys and Megalonema. The composition for the Pimelodus group is Pimelodus, Bergiaria, Iheringichthys and Parapimelodus and for Exallodontus group is Exallodontus, Propimelodus, Duopalatinus peruanus, Pimelodus altissimus, andmore six new species. Based on the new rearrangements, a list of all valid genera and their species, diagnosis and distribution is given.
Keywords: Pimelodidae; Taxonomia da família Pimelodidae